ANALISIS EFEKTIFITAS DAN EFISIENSI PENGELOLAAN KEUANGAN DESA (STUDI PADA DESA DI KABUPATEN DELI SERDANG) - Fachrul Amanullah Siregar; Fazli Syam BZ (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
Undang-Undang Nomor 6 Tahun 2014 on Villages explains that the Village is a legal community unity that has territorial boundaries to administer and administer government affairs, the interests of local communities based on traditional. Villages have the authority to organize and manage the interests of their own communities according to local conditions and social culture. The purpose of this study based on the formulation of the problems that have been stated above is to measure the level of effectiveness and efficiency of village finances in Deli Serdang District and Village Financial Management in Deli Serdang District and provide recommendations to overcome the problem. The type of this research is qualitative research. Qualitative research is research, where researchers collect and analyze data, integrate findings, and draw inferential conclusions using qualitative research methods in one study. In terms of effectiveness of financial performance development based on the use of ADD in 2016 seen that there are differences in the effectiveness level almost all villages used as research samples have a ratio of 100% or Effective, only a few villages that have a very low level of effectiveness such as Medan Estate village which has the effectiveness ratio of 69% or Less Effective, as well as the effectiveness analysis of DD use in 2016, which shows that the average use of DD has a ratio of 100% or Effective, it's just that some villages also seen still have a low level of effectiveness, such as village Bangun Sari has an effectiveness ratio of 31% or Not Effective, as well as Bintang Meriah village which only has a level of effectiveness ratio of 73% or Less Effective